Evaluasi Kriteria Kerusakan tanah untuk Produksi Biomassa pada Lahan Kering di Kabupaten Subang - Budy Frasetya Taufiq Qurrahman; Abraham Suriadikusumah; Rachmat Haryanto (Fakultas Pertanian Universitas Padjadjaran, 2016)
Government Regulation No. 150 Year 2000 on Soil Degradation Control for Production of Biomass is a testament to the seriousness of the government in anticipating and addressing land degradation due to biomass production. In fact, unsustainable intensification can cause soil degradation. Soil degradation parameters may change in accordance with the conditions of the district/city. This study aimed to evaluate the standard criteria of soils degradation on dry land in Subang District. Did having high accuracy and whether the ten parameters are decisive parameters. The research method used was a descriptive survey. Data from the field and then analyzed using discriminant analysis. The results of discriminant analysis for soil degradation standard criteria in Subang District, determining parameters were selected 4 parameters, ie bulk density, sand fraction,electrical conductivity, soil reaction (pH) with the level of accuracy obtained discriminant function 74,1 % with corelation coeficient 0,866 or 86,6 % and determination coeficient (R2) 0,75 or 75 %. Keywords: Accuracy Discriminant Function, Evaluation Standards Criteria, Parameters Determinant